2019
DOI: 10.22606/tp.2019.43002
|View full text |Cite
|
Sign up to set email alerts
|

Nonthermal Distribution of Electro-negative Light-ions in Heavy-ion-acoustic Solitary and Shock Structures

Abstract: An attempt has been taken to study the nonlinear propagation of electro-positive heavy ion-acoustic (EPHIA) solitary and shock waves in multi-component plasmas containing mobile electro-positive heavy ions (EPHIs), nonthermal distributed electro-negative light ions (ENLIs) and Maxwellian electrons. The effects of temperature, mobile EPHIs, ENLIs and its nonthermality on solitary and shock waves are investigated in present work. To do so, we have derived the standard Korteweg-de Vries (K-dV) and Burger equation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 22 publications
0
1
0
Order By: Relevance
“…The non-thermal plasma species are regularly seen in the cometary comae [2], Earth's ionosphere [4], the upper region of the Titans [3], etc. Haider et al [27] investigated the IA solitary waves in the presence of non-thermal particles, and observed that the width of the solitary profile decreases with increasing of ions' non-thermality. Pakzad and Javidan [28] studied the dustacoustic (DA) solitary and shock waves in a dusty plasma having non-thermal ions, and reported that the amplitude of the wave increases with the decrease of the non-thermality of ions.…”
Section: Introductionmentioning
confidence: 99%
“…The non-thermal plasma species are regularly seen in the cometary comae [2], Earth's ionosphere [4], the upper region of the Titans [3], etc. Haider et al [27] investigated the IA solitary waves in the presence of non-thermal particles, and observed that the width of the solitary profile decreases with increasing of ions' non-thermality. Pakzad and Javidan [28] studied the dustacoustic (DA) solitary and shock waves in a dusty plasma having non-thermal ions, and reported that the amplitude of the wave increases with the decrease of the non-thermality of ions.…”
Section: Introductionmentioning
confidence: 99%